(untitled) (Journal of the College of Basic Education, 2023)
The progress and advancement of societies depends mainly on what society possesses ofhuman power capable of exploiting its natural resources in the best possible way, and education isOne of the important means to eradicate backwardness and walk in the path of civilization and progress, because of itsIt plays a major role in the development of the individual’s personality in all mental, emotional and psychological aspects.and physical, and help him to adapt positively to the natural and social environment, and the most importantThe researcher of education is the teacher, as his role is considered one of the most important factors influencing the student’s behavior and on him.The success of the educational process depends on the progress and sophistication of society.The science teacher, in order to successfully play his role in the educational process, must have the competencies and skillsIn addition to his possession of sufficient information, the most important of these skills is the skill of interrogation orQuestioning, and that the efficiency of teaching is measured to a large extent by the nature of the question asked. Therefore, the research aimsThe current study aims to identify the interrogation skills of biology teachers through building a toolTo measure these skills by observing the behavior of the research sample, and its validity was found fromDuring its presentation to a group of experts and arbitrators, its stability was found to be (0.82).The tool included (37) items distributed in three areas: (asking questions, receivingThe answers, organizing the classroom atmosphere) are five alternatives. The research sample consisted of (23)Male and female teachers from (23) schools, the tool was applied to them on 25/2/2002.The following statistical methods (Scott’s correlation coefficient, the arithmetic mean, the weighted mean(weight percentile). Among the results of the study is that there are (37) skills that emphasizeteachers to use them, and the following skills ranked first (asking relevant questionsRelevancy to the topic and objectives of the lesson. Repeat the answer to the question in a manner that all students understand.Students can answer without permission). In the light of the research results, several recommendations and proposals were made.